2018
DOI: 10.1186/s12967-018-1673-6
|View full text |Cite
|
Sign up to set email alerts
|

CD25 and TGF-β blockade based on predictive integrated immune ratio inhibits tumor growth in pancreatic cancer

Abstract: BackgroundThe prognosis of pancreatic ductal adenocarcinoma (PDAC) remains poor due to the difficulty of disease diagnosis and therapy. Immunotherapy has had robust performance against several malignancies, including PDAC. In this study, we aim to analyze the expression of CD8 and FoxP3 on T lymphocytes and TGF-β expression in tumor tissues, and then analyze the possible clinical significance of these finding in order to find a novel effective immunotherapy target in PDAC using a murine model.MethodsA tissue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Infiltrating FoxP3+ regulatory T cells (Tregs) in tumor tissues are considered a major obstacle to clinical efficacy of tumor immunotherapy and associated with a poor prognosis. 44 45 The ability of galunisertib to block the suppressive activity of human Tregs has been demonstrated in vitro 46 but has not yet been observed clinically. Additional studies examining tumor microenvironment characteristics may be warranted to increase the efficiency of PD-1 immunotherapy and improve the prognosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltrating FoxP3+ regulatory T cells (Tregs) in tumor tissues are considered a major obstacle to clinical efficacy of tumor immunotherapy and associated with a poor prognosis. 44 45 The ability of galunisertib to block the suppressive activity of human Tregs has been demonstrated in vitro 46 but has not yet been observed clinically. Additional studies examining tumor microenvironment characteristics may be warranted to increase the efficiency of PD-1 immunotherapy and improve the prognosis of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The blood parameters reflect the anti-factor and promoting-factor of inflammatory response and immune response to the cancer 16 . Our previous study had investigated the changes of microenvironment in PDAC, which showed the prognosis-related changes of regulatory T cells and CD8 + T cells 22 . Our present research indicated that elevated poNLR was an independent predictive factor to the prognosis of PDAC undergoing ODPS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an increased number of IFN-γ+CD8+ T cells are also an indicator of the successful combination treatment of bintrafusp alfa and radiotherapy [ 150 ]. Pu et al have identified an integrated immune ratio based on the number of infiltrating CD8+ T cells and FOXP3+ Tregs to predict tumour suppression in the combination immunotherapy of CD25, TGF-β, and PD-1 blockade [ 174 ]. In melanoma, the treatment mediated by TGFBR1 inhibitor SB505124 in the presence of IL-12 overexpression demonstrates enhanced immune responses, and NK1.1 is a potential biomarker for increased effector cells and enhanced cancer-killing effects [ 175 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%